Breakdown of Varvenne scaling in (AuNiPdPt)1−xCux high-entropy alloys. (May 2020) - Thiel, F.; Utt, D.; Kauffmann, A.; Nielsch, K.; Albe, K.; Heilmaier, M.; Freudenberger, J.
Highlights: ( AuNiPdPt ) 1 − x Cu x forms a homogeneous solid solution with deliberately adjusted Cu concentration. Investigation of concentration-dependent solid solution strengthening in concentrated solid solutions. The yield strength of ( AuNiPdPt ) 1 − x Cu x decreases linearly with x, while theory predicts an increase and non-linear scaling. The absolute values of the yield strength and their range across x are much higher when compared to theory. Graphical abstract: Abstract: The compositional dependence of the yield strength σy has been studied for a series of polycrystalline ( AuNiPdPt ) 1 − x Cu x alloys by means of compression tests. σy is found to decrease linearly with increasing Cu concentration. This behaviour is in contradiction to the generalised theory for solid solution strengthening in concentrated solid solutions provided by Varvenne et al. [1]. A breakdown of the scaling behaviour is found as σy should be non-linear and slightly increasing when modifying the composition from AuNiPdPt to AuCuNiPdPt.